PENINGKATAN KUALITAS PEMBELAJARAN DOSEN MELALUI PENUGASAN DI SEKOLAH - Muryanto, Hagus; Srijani, Ninik; Nugraha, Nurhadji; Parji, Parji; Kiswardianta, R. Bekti (Jurnal Pendidikan, 2008)
The quality of products of a Teacher Training Institution does not merely depend on the grade point everage they pursue, but also on the competitive advantage they gain during the learning process to fight for position and apply the pedagogical priciples in the work market share. The quality of teaching and learning process in the campus should be then fitted to such needs of the market share, which can be done by sending lecturers to schools as apprentice teachers.This Peer Grant Research is aimed at: 1) developing the quality of lecturers instruction, 2) developing relationship between IKIP PGRI Madiun and the peer institutions, 3) searching and implementing alternative strategies for teaching and learning effectiveness. Collaborative teaching between lecturers of IKIP PGRI Madiun and teachers of SMP N 11 Madiun is designed to: 1) observe the existing condition of classes, 2) discuss for developing alternative strategies, 3) arrange and implement the instructional design, 4) conduct teaching and learning process, and 5) suggest evaluation. Class observation, questionaire and interview are used to draw data from 7 subjects in research, i.e.: Bahasa Indonesia, English, Natural Science, Social Science, Math, Civics and Counseling.The results of the research can be outlined as follows: 1) lecturers develop their classes by inspecting and implementing directly the instruction in real scholls classes, 2) identification against weaknesses in schools classes can be arranged for further evaluation, 3) the campus develops teacher training instructional designs based on field inventions, 4) collaborative team invent alternative strategies in classes, 5) lecturers experience real schools classes so as to develop their instructional design, 6) teachers are motivated to continously develop their teaching to gain optimal out-come.Key words: quality, learning, apprenticeship, lectures